2016
DOI: 10.1002/advs.201600229
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Metastatic and Anti‐Angiogenic Activities of Core–Shell SiO2@LDH Loaded with Etoposide in Non‐Small Cell Lung Cancer

Abstract: Currently, nanoparticles have gained a great attention in the anti‐tumor research area. However, to date, studies on the anti‐metastasis action of core–shell SiO2@LDH (LDH: layered double hydroxide) nanoparticles remain untouched. Two emerging aspects considered are establishing research on the controlling delivery effect of SiO2@LDH combined with anti‐cancer medicine from a new perspective. The fine properties synthetic SiO2@LDH‐VP16 (VP16: etoposide) are practiced to exhibit the nanoparticle's suppression on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…The AgNPs inhibit the VEGF-induced angiogenesis by blocking the formation of new microvessels through PI3K/AKT pathway inactivation ( 118 ). It has been demonstrated that the anionic clays layered double hydroxides (LDHs), a promising carrier for drug delivery according to their low cytotoxicity and high biocompatibility ( 119 ): their functionalized form with etoposide has showed anti-angiogenic activity in in vitro , ex-vivo and in vivo experimental models, eliciting depression of the PI3K-AKT and FAK-paxillin signaling pathways ( 120 ). Modified solid lipid nanoparticles loaded with paclitaxel were able to markedly reduce the tube formation in vitro and angiogenesis in vivo in glioma models ( 121 ), while, in a chorioallantoic membranes model system, pachymic acid modified multi-walled nanotubes caused a significant inhibition of angiogenesis and tube formation ( 122 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…The AgNPs inhibit the VEGF-induced angiogenesis by blocking the formation of new microvessels through PI3K/AKT pathway inactivation ( 118 ). It has been demonstrated that the anionic clays layered double hydroxides (LDHs), a promising carrier for drug delivery according to their low cytotoxicity and high biocompatibility ( 119 ): their functionalized form with etoposide has showed anti-angiogenic activity in in vitro , ex-vivo and in vivo experimental models, eliciting depression of the PI3K-AKT and FAK-paxillin signaling pathways ( 120 ). Modified solid lipid nanoparticles loaded with paclitaxel were able to markedly reduce the tube formation in vitro and angiogenesis in vivo in glioma models ( 121 ), while, in a chorioallantoic membranes model system, pachymic acid modified multi-walled nanotubes caused a significant inhibition of angiogenesis and tube formation ( 122 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…Unfortunately, the prognosis of regular chemotherapy is usually unsatisfactory due to a series of situations, including tumor metastasis, vasculogenic mimicry (VM) channels, limited killing of tumor cells, and severe systemic toxicity. 7 VM channels were first found in highly aggressive and metastatic melanoma cells in 1999. 8 Under the condition of hypoxia, tumor cells could directly form VM channels, thus facilitating tumor metastasis without the involvement of endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] There are several studies showing that the anticancer effect of Etoposide is enhanced on different cancer cell lines using a nanoparticle delivery system. [17][18][19][20][21] Due to the hydrophobic nature of the drug PLGA and PCL were often used. For example, 11.8 micron PLGA nanoparticles loaded with Etoposide were evaluated for sustained pulmonary drug delivery.…”
Section: Introductionmentioning
confidence: 99%